2021
DOI: 10.3390/ijerph182413137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevation and Distance from Highway on the Abundance and Community Structure of Bacteria in Soil along Qinghai-Tibet Highway

Abstract: In recent years, highway construction in the Qinghai-Tibet Plateau (QTP) has developed rapidly. When the highway passes through grassland, the soil, vegetation, and ecological environment along the line are disturbed. However, the impact on soil bacteria is still unclear. Soil bacteria play an important role in the ecological environment. The Qinghai-Tibet Highway (QTH) was selected as the research object to explore the changes in bacterial community structure, vegetation, soil, and other indicators. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Studies have shown that as the distance to roads increases, there are fewer changes in land use and land cover change (Patarasuk & Binford, 2012). Elevation, on the other hand, can affect land cover change through its impact on vegetation and soil conditions (Liu et al, 2021) The results of the altitude and distance to the road can be seen in Figures 3 and 4. The altitude in Banjarbaru is included in the lowland category with an altitude of 0-380 meters.…”
Section: Resultsmentioning
confidence: 98%
“…Studies have shown that as the distance to roads increases, there are fewer changes in land use and land cover change (Patarasuk & Binford, 2012). Elevation, on the other hand, can affect land cover change through its impact on vegetation and soil conditions (Liu et al, 2021) The results of the altitude and distance to the road can be seen in Figures 3 and 4. The altitude in Banjarbaru is included in the lowland category with an altitude of 0-380 meters.…”
Section: Resultsmentioning
confidence: 98%
“…Blastococcus species have been identified as key components in soils facing diverse challenges, including dryness [2][3][4][5][6][7][8][9][10][11], salinity [43], alkalinity [44], exposure to toxins [45], and notably, heavy metal contamination [46][47][48][49][50]. Consequently, the distribution of genes associated with stress response, antibiotic resistance, as well as resistance to heavy metals and toxic compounds, were evaluated within these genomes.…”
Section: Genomic Prediction Of Ecological Features and Secondary Meta...mentioning
confidence: 99%
“…The genus comprises 14 validly named species, each isolated from various sources. Members of Blastococcus have been identified as pivotal organisms in soils facing diverse challenges, including salinity [4], alkalinity [5], exposure to toxins [6] and, notably, heavy metal contamination [7][8][9][10][11]. Their remarkable adaptability and versatility position Blastococcus species as valuable resources with significant biotechnological potential, encompassing applications in bioremediation, bioleaching, agriculture, enzyme production and the production of potential bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%